The Determinants of Hedging by Derivatives in Hong Kong and Chinese Firms and the Value Effects - SHIYUN, CHEN (2015)
This dissertation studies the determinants and the value effects of corporate hedging with derivatives for 230 Hong Kong and Chinese non-financial firms listed in Hong Kong Stock Exchange from 2008 to 2013. With the data from annual reports, the evidence is found that there are positive relations between deciding to hedge with derivatives and foreign currency exposures, expected cost of financial distress, and scale of economies. The liquidity measures are negatively linked with the usage of derivatives. The empirical results of the financial distress costs and liquidity factors for Chinese firms are relatively weaker than those of Hong Kong firms, which may be explained by the state and the government as the major shareholder providing financial supports and the debt guarantee. Finally, the growths of firm values from hedging activities are 1.70% for Hong Kong firms and 0.37% for Chinese firms from the perspective of tax benefits.